Ventajas y desventajas del uso de anestésico local con vasoconstrictor y sin vasoconstrictor en odontología. revisión sistemática - Albán Real, César Ismael (2025)
Local anesthetics are currently used to block nerve impulse conduction in a reversible manner. Currently, the most commonly used anesthetic drugs in dentistry are lidocaine at 2% plus epinephrine with a concentration of 1:80,000, mepivacaine at 3% and prilocaine at 4%. Objective: To describe the advantages and disadvantages of the most commonly used local anesthetics with and without vasoconstrictor agent in dentistry. Materials and method: The study has a qualitative and descriptive approach, through a review of the literature and an exhaustive analysis using scientific database: PubMed, BVS, Google Academic, Cochrane Library and Scielo. Results: A total of 104 articles was compiled, based on exclusion and inclusion criteria, following PRISMA parameters. 16 relevant articles and 2 books updated to their latest edition were included. Conclusion: The use of local anesthetics with vasoconstriction agent gives security and a better operating field in any dentistry procedure. Lidocaine at 2% plus epinephrine with a concentration of 1:80,000 and 1:100,000; Mepivacaine at 3% and Prilocaine at 4% without any vasoconstriction agent are the most commonly used local anesthetics in dentistry.